Oxygen Ion Implantation Improving Cell Adhesion on Titanium Surfaces through Increased Attraction of Fibronectin PHSRN Domain. Issue 10 (18th February 2022) - Shi, Miusi; Mo, Wenting; Qi, Haoning; Ni, Yueqi; Wang, Rui; Shen, Kailun; Zhang, Fanyu; Jiang, Shuting; Zhang, Xuehui; Chen, Lili; Zhang, Yufeng; Deng, Xuliang
Abstract: Mechanistic understanding of fibronectin (FN) adsorption which determines cell adhesion on cell–implant interfaces is significant for improving the osteoconduction and soft‐tissue healing of implants. Here, it is shown that the adsorption behavior of FN on the titanium oxide surface (TiO2 ) is highly relative to its Pro‐His‐Ser‐Arg‐Asn (PHSRN) peptide. FN lacking PHSRN fails to bind to surfaces, resulting in inhibited cell adhesion and spreading. Molecular dynamics simulation shows higher affinity and greater adsorption energy of PHSRN peptide with TiO2 surface due to the stronger hydrogen bonds formed by the serine and arginine residues with O ion of the substrate. Finally, by increasing O content in TiO2 surfaces through O ion‐beam implantation, improving the cell adhesion, cell differentiation, and the subsequent biomineralization on titanium implant is realized. This study reveals the vital role of PHSRN in FN‐mediated cell adhesion on implant surfaces, providing a promising new target for further tissue integration and implant success. Abstract : PHSRN domain on the 9–10th type III repeat of fibronectin is essential for the protein adsorption on implant surface through strong hydrogen bond formation between serine and arginine residues with O ions of substrate. Increasing O ion content on titanium surfaces by ion beam implantation could amplify the fibronectin adsorption, promoting cell adhesion and final biomineralization outcomes.